ENGINEERING PEDAGOGY: FROM COLLABORATIVE LEARNING TO UNIVERSAL SYNERGY - P. N. Osipov (Высшее образование в России, 2017)
The labor market imposes new requirements to a contemporary engineer: he should be capable of working in groups and managing other people, ready for teamwork, independent decision making, setting and solving new professional problems, independent investigation and implementation of professional innovations. These competencies should be developed at universities. Any pedagogical system exists by means of collaboration between professors and students, between students themselves, i.e. implies collaborative learning thus leading to personal growth of educational process participants. Students develop a positive and active attitude towards their future professional responsibilities only by setting and reaching cognitive goals. Collaborative learning technologies contribute to the formation of this attitude. The paper focuses on the detailed mechanisms of collaborative learning technologies at different levels of education – from teaching and learning processes at special college to international research collaboration between professors. The author shows the collaborative learning contribution to universal synergy.